2023
DOI: 10.1002/jha2.736
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune reconstitution following therapy with daratumumab, carfilzomib, lenalidomide, and dexamethasone (Dara‐KRd), autologous hematopoietic cell transplantation, and measurable residual disease‐response‐adapted treatment cessation

Abstract: Quadruplet induction, autologous hematopoietic cell transplant (AHCT), and measurable residual disease (MRD) response‐adapted consolidation yield an unprecedented depth of response in newly diagnosed multiple myeloma. Patients treated on MASTER (NCT03224507) ceased therapy and entered active surveillance (MRD‐SURE) after achieving MRD negativity. This study characterizes quantitative changes in the immunoglobulin (Ig) gene repertoire by next‐generation sequencing and serum gamma globulin levels. Quadruplet the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…We anticipate that results from the ongoing MRD2STOP study (NCT04108624), in which patients who achieve sustained MRD negativity at 10 −6 sensitivity level combined with undetectable M‐spike and no evidence of disease by positron emission tomography can discontinue maintenance treatment will further help to unravel the effect of not only de‐escalation but also a cessation of lenalidomide maintenance on humoral immunity. It will be particularly interesting in the context of recently published results documenting humoral immune reconstitution in patients who discontinued quadruplet, carfilzomib‐containing therapy after achieving MRD negativity, 27 with our data suggesting that this effect may be mostly driven by the discontinuation of the proteasome inhibitor.…”
Section: Discussionsupporting
confidence: 51%
“…We anticipate that results from the ongoing MRD2STOP study (NCT04108624), in which patients who achieve sustained MRD negativity at 10 −6 sensitivity level combined with undetectable M‐spike and no evidence of disease by positron emission tomography can discontinue maintenance treatment will further help to unravel the effect of not only de‐escalation but also a cessation of lenalidomide maintenance on humoral immunity. It will be particularly interesting in the context of recently published results documenting humoral immune reconstitution in patients who discontinued quadruplet, carfilzomib‐containing therapy after achieving MRD negativity, 27 with our data suggesting that this effect may be mostly driven by the discontinuation of the proteasome inhibitor.…”
Section: Discussionsupporting
confidence: 51%
“…In our study, we set a cut‐off of 6 months to divide Dara and non‐Dara cohorts as some studies showed that there might be a marked recovery of immunoglobin and natural killer cells approximately 6 months after discontinuation of Dara‐based treatment. 36 , 37 The rates of severe COVID‐19 and COVID‐19‐related mortality were 25.6% and 7.7%, respectively, in the overall Dara cohort. In both univariate and multivariate analyses, the use of Dara within 6 months was a risk factor for severe COVID‐19.…”
Section: Discussionmentioning
confidence: 97%
“…However, the outcome of patients treated with anti‐38 Abs after COVID‐19 infection is not clear. In our study, we set a cut‐off of 6 months to divide Dara and non‐Dara cohorts as some studies showed that there might be a marked recovery of immunoglobin and natural killer cells approximately 6 months after discontinuation of Dara‐based treatment 36,37 . The rates of severe COVID‐19 and COVID‐19‐related mortality were 25.6% and 7.7%, respectively, in the overall Dara cohort.…”
Section: Discussionmentioning
confidence: 99%